2007
DOI: 10.1111/j.1365-2699.2007.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting species distributions from herbarium collections: does climate bias in collection sampling influence model outcomes?

Abstract: Aim Species distribution models and geographical information system (GIS) technologies are becoming increasingly important tools in conservation planning and decision-making. Often the rich data bases of museums and herbaria serve as the primary data for predicting species distributions. Yet key assumptions about the primary data often are untested, and violation of such assumptions may have consequences for model predictions. For example, users of primary data assume that sampling has been random with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
224
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(238 citation statements)
references
References 50 publications
(67 reference statements)
5
224
0
9
Order By: Relevance
“…Especially during the early part of the 20th century, Rhododendron was also of great horticultural value in Europe and North America (26). Originally gathered for species delimitation, historical herbarium collections have been used to impute changes in species ranges (27,28) and in traits (29,30). Specimens were usually collected in flower and with data on time and place of collection.…”
mentioning
confidence: 99%
“…Especially during the early part of the 20th century, Rhododendron was also of great horticultural value in Europe and North America (26). Originally gathered for species delimitation, historical herbarium collections have been used to impute changes in species ranges (27,28) and in traits (29,30). Specimens were usually collected in flower and with data on time and place of collection.…”
mentioning
confidence: 99%
“…Our ability to predict species' abundances and ranges, let alone how they will change, remains limited [18,22]. In order for biologists to predict how individual taxa and entire communities will respond to a changing world requires understanding why plant taxa grow where they do and what limits their ranges.…”
Section: -The Grand Challenge: In a Changing World What Grows Whementioning
confidence: 99%
“…It is presumed to be one of the factors potentially distorting the results of biogeographical analysis (Funk & Richardson 2002, Loiselle et al 2008, Wolmarans et al 2010), but its influence on model output is rarely explicitly made. However, it has been demonstrated that spatial bias can have a substantial influence on model outcome and performance as well as in the establishment of the effect of environmental variables on the defined niche of a species (Graham et al 2004, Feeley & Silman 2010.…”
Section: Bias: a Recurrent Issuementioning
confidence: 99%